Effects of interaction between arbuscular mycorrhizal fungi, rhizobacteria, soil phosphorus and plant cytokinin content on tobacco growth - Cosme, Marco Paulo Rebeca (2010)
Mestrado em Engenharia Florestal e dos Recursos Naturais - Instituto Superior de Agronomia